Practical Management of Pediatric Ocular Disorders and Strabismus : a Case-based Approach. - Traboulsi, Elias (Springer New York, 2016)
This case-based approach to the management of pediatric eye diseases and strabismus teaches the novice, as well as the experienced surgeon, how to conceptualize and analyze surgical planning to maximize patient outcomes, allowing readers to "get inside the head of the surgeon." Individual cases with clear instructions and an abundance of color illustrations, presented by experts in the field, teach critical information one case at a time. Practical Management of Pediatric Ocular Disorders and Strabismus provides the key guiding principles of a traditional textbook in an easy-to-digest format. Each chapter of the text tackles a common or rare clinical situation and begins with the description of an illustrative case. The chapters are structured with sections on case description, differential diagnosis, management and outcomes with a list of possible complications and the approach to their management